Sistem Destinasi Pariwisata di Kabupaten Bogor Jawa Barat - Firman Syah (Majalah Ilmiah Bijak, 2017)
The existing tourist destination system in Bogor Regency basically has entered the integral of existing development, so that it can be accessed by the whole world. The influence of the concept of tourism development basically increases the acceleration of development and economy in a large area. This causes the development of tourism in Bogor Regency as one of the priority sectors.To obtain accurate and current data, the authors conduct research directly in the field using qualitative methods that are inductive. The results show that the existing tourist destination system in Bogor Regency implemented basically been running as it should. However, when compared with tourist villages outside of Bogor Regency such as Gunungkidul Regency in Yogyakarta obviously still far behind.The advantages and disadvantages that exist in the tourist destination system is the Village Information System (SID) that has not been maximized as the existence of a planned website as the system that runs in Gunungkidul Regency. So that the visiting domestic tourists are still from Jakarta, Depok, Tangerang, and Bekasi. For that, the village tour continues to conduct comparative studies in addition to Yogyarakata also to Cibuntu in Kuningan, including professional certification.